Ireland and the fiction of improvement - O'Connell, Helen, 1949- (Oxford University Press, 2006)
Presenting a study of 'improving' fiction produced in Ireland in the 19th century, this work demonstrates how this pamphlet literature shaped the mainstream literary culture. It also sheds light on the work of Maria Edgeworth, Mary Leadbeater, William Carleton, Thomas Davis, J.M. Synge, W.B. Yeats, and others.